2017
DOI: 10.1371/journal.pone.0190159
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the acute inflammatory profile and resolution of airway inflammation after Igf1r-gene targeting in a murine model of HDM-induced asthma

Abstract: Asthma is a chronic inflammatory disease characterized by bronchial hyperresponsiveness, mucus overproduction and airway remodeling. Notably, we have recently demonstrated that insulin-like growth factor 1 receptor (IGF1R) deficiency in mice attenuates airway hyperresponsiveness and mucus secretion after chronic house dust mite (HDM) exposure. On this basis, inbred C57BL/6 and Igf1r-deficient mice were given HDM extract to study the acute inflammatory profile and implication of Igf1r in acute asthma pathobiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 41 publications
(69 reference statements)
4
18
0
Order By: Relevance
“…In contrast, Igfbp2 and Igfbp4 expression depends solely on IGF1R activation since they were only found diminished by NVP treatment. Increased expression of Igf1 by HDM, which lowered to basal levels upon treatment with NVP, is in accordance with our previous findings [ 16 ]. HDM-mediated induction of Igf1 could be responsible for IGF1R phosphorylation to promote the asthmatic response, and therefore supports why targeting IGF1R with NVP ameliorates HDM-induced asthma.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, Igfbp2 and Igfbp4 expression depends solely on IGF1R activation since they were only found diminished by NVP treatment. Increased expression of Igf1 by HDM, which lowered to basal levels upon treatment with NVP, is in accordance with our previous findings [ 16 ]. HDM-mediated induction of Igf1 could be responsible for IGF1R phosphorylation to promote the asthmatic response, and therefore supports why targeting IGF1R with NVP ameliorates HDM-induced asthma.…”
Section: Discussionsupporting
confidence: 93%
“…HDM-induced allergy has been successfully proven for the study of asthma pathobiology [ 15 , 16 , 24 ]. Therefore, we deemed that our asthma model was appropriate for testing the in vivo anti-asthmatic efficacy of IGF1R inhibition using the IGF1R TKI inhibitor NVP-ADW742 (NVP).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 HDM exerts its inflammatory response via Der p 1, 3, 5, and 9 antigens by stimulating airway epithelium to produce Th1/Th2 inflammatory response through protease-activated receptor-2 mediated mechanism. [18][19][20][21] While there are several commercial HDM allergens, we utilized Greer extract in our studies as it is one of the most characterized 12,18,22 and induces pronounced increases in CCL20, CCL17 and interleukin 5 accompanied by HDM-specific IgE, goblet cell hyperplasia, eosinophilic inflammation and airway hyper-reactivity. 23 In the present study, we attempted to systematically characterize HDM-induced F I G U R E 7 Expression of inflammatory genes in BAL cells after HDM challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In a model of asthma, a well-known inflammatory disease, Shao et al demonstrated that miR-133a is downregulated in this inflammatory niche and activates IGF-1R signaling, which is responsible for airway remodeling in asthma (Shao et al, 2019 ). IGF-1R deletion reduces the infiltration of immune cells as well as the expression of inflammation markers in the lung tissues in a murine model of asthma (Pineiro-Hermida et al, 2017 ). In addition, niche inflammation modulates IGF-1R signaling and affects local cellular responses.…”
Section: Igf-1r Signaling and Niche Interactionmentioning
confidence: 99%